CD4+ Tissue-resident Memory T Cells Expand and Are a Major Source of Mucosal Tumour Necrosis Factor α in Active Crohn's Disease. (4th February 2019) - Bishu, Shrinivas; El Zaatari, Mohammed; Hayashi, Atsushi; Hou, Guoqing; Bowers, Nicole; Kinnucan, Jami; Manoogian, Beth; Muza-Moons, Michelle; Zhang, Min; Grasberger, Helmut; Bourque, Charlie; Zou, Weiping; et al.
Abstract: Background and Aims: Tumour necrosis factor [TNF]α- and IL-17A-producing T cells are implicated in Crohn's disease [CD]. Tissue-resident memory T [TRM ] cells are tissue-restricted T cells that are regulated by PR zinc finger domain 1 [PRDM1], which has been implicated in pathogenic Th 17 cell responses. TRM cells provide host defence but their role in CD is unknown. We thus examined CD4 + TRM cells in CD. Methods: Colon samples were prospectively collected at endoscopy or surgery in CD and control subjects. Flow cytometry and ex vivo assays were performed to characterise CD4 + TRM cells. Results: CD4 + TRM cells are the most abundant memory T cell population and are the major T cell source of mucosal TNFα in CD. CD4 + TRM cells are expanded in CD and more avidly produce IL-17A and TNFα relative to control cells. There was a unique population of TNFα + IL-17A + CD4 + TRM cells in CD which are largely absent in controls. PRDM1 was highly expressed by CD4 + TRM cells but not by other effector T cells. Suppression of PRDM1 was associated with impaired induction of IL17A and TNFA by CD4 + TRM cells Conclusions: CD4 + TRM cells are expanded in CD and are a major source of TNFα, suggesting that they are important in CD. PRDM1 is expressed by TRM cells and may regulate their function. Collectively, this argues for prospective studies tracking CD4 + TRM cells over the disease course.